Agricultural economics - Drummond, H. Evan (Prentice Hall, 2004)
This provides knowledge about agricultural economics from a broad perspective that emphasizes the linkages between and among financial institutions, the macro economy, world markets, government programs, farms, agribusinesses, food marketing, farm services, and the environment.